The Role of (Intra-)Discal Treatments for Discogenic Low Back Pain. (May 2014) - Bendix, Tom
The intervertebral disc is believed to be the key pathology behind low back pain (LBP). The pain mechanisms include annular ruptures, fissures in the end plates, neural sensors on the disc surface causing muscle stimulation, 1 in combination with various biochemical reactions, particular involving cytokines. Disc herniations are not dealt with this review. The ruptures/fissures in the annulus and end plates may cause pain directly, if annular ruptures reach the disc surface. Beside these classical physical aspects, it is increasingly clear that inflammatory cytokines play a role. 2 Also, there are convincing indications that the cytokine TNF-α passes the annular ruptures and irritates the disc surface. 3 The newest recognized pathology is that end plate ruptures may give rise to modic changes, possibly caused by low-virulent anaerobic bacteria. Intradiscal treatments have been used and tested over the years. The theories behind the first such treatments, chymopapain and intra-discal electro-thermal therapy (IDET), was the mechanical issue that the jelly-like and toxic nuclear material may penetrate through the annular ruptures. Probably, Mother Nature has decided that when annular ruptures become a problem, nucleus should be more fibrotic preventing its penetration. If this fibrosing can be accelerated in an early degenerated phase, part of the problem might be reduced. Later years, injection treatments rather consider the biochemical aspects. Such treatments will briefly be discussed in the article. For them all, the demonstrated likelihood of later developed degeneration is a potential disadvantage for any intradiscal injection. 4 Chymopapain There is still some evidence for its value in herniated discs although this is less beneficial than surgery. Regarding back pain, studies are not sufficient to conclude its possible relevance. Intradiscal Electro-Thermal Therapy The hypothesis is that a fibrosing of the nucleus, or a closening of ruptures at the inner annulus wall, would decrease the likelihood of nucleus' penetration through annular ruptures. As often seen, the first RCT showed a bright effect, but the following three only a small or no effect at all. A meta-analysis and further discussion questions a relevant clinical effect. 5 Methylene Blue In 2010, Peng et al published a remarkable RCT showing a tremendous LBP and Oswestry reduction remaining at 2 years follow-up. Whereas, the controls only dropped slightly. 6 The debate has been tremendous, and later small, open series failed to be that positive, one only a short effect, the other no effect. Status is that most centers are waiting for ongoing further studies. Stem cells Stem cells are probably a perspective area. However, it may not be beneficial to regenerate nucleus if it is true that it becomes fibrotic to reduce its protrusion through annular ruptures. More logical would it be to regenerate annulus, which seems more difficult. So far, no RCT exists illustrating optional clinical value. Steroid The evidence for intradiscal steroid injections in "usual" discogenic back pain is weak. 7 However, in case of MC-1 changes two small moderate-sized studies indicated significant clinical effects. 8 This conclusion has to be verified further, but most remarkably: if the bacteria theory is true, no infectious flare up was observed. Antitumor Necrosis Factorα One of two RCTs on discogenic pain without MCs with intradiscally etanercept revealed some positive effect (Sainoh, ISSLS 2013). Local treatment on the outside of the disc has in a small, randomized study, intending to test leg pain in herniation, also showed reduction in back pain. 9 Antibiotics The highly perspective study on MC-1 (presented by Albert at this congress) actually also represents an intradiscal treatment, although it is executed by peroral application, but over so long time that it is considered to penetrate into the nucleus. Disclosure of Interest None declared References Indahl A. Low back pain: diagnosis, treatment, and prognosis. Scand J Rheumatol 2004;33(4):199–209 Chan WC, Sze KL, Samartzis D, Leung VY, Chan D. Structure and biology of the intervertebral disk in health and disease. Orthop Clin North Am 2011;42(4):447-464, vii Olmarker K. Puncture of a disc and application of nucleus pulposus induces disc herniation-like changes and osteophytes. An experimental study in rats. Open Orthop J 2011;5:154–159 Carragee EJ, Don AS, Hurwitz EL, Cuellar JM, Carrino JA, Herzog R. 2009 ISSLS Prize Winner: Does discography cause accelerated progression of degeneration changes in the lumbar disc: a ten-year matched cohort study. Spine 2009;34(21):2338–2345 Helm S, Hayek SM, Benyamin RM, Manchikanti L. Systematic review of the effectiveness of thermal annular procedures in treating discogenic low back pain. Pain Physician 2009;12(1):207–232 Peng B, Pang X, Wu Y, Zhao C, Song X. A randomized placebo-controlled trial of intradiscal methylene blue injection for the treatment of chronic discogenic low back pain. Pain 2010;149(1):124–129 Khot A, Bowditch M, Powell J, Sharp D. The use of intradiscal steroid therapy for lumbar spinal discogenic pain: a randomized controlled trial. Spine 2004;29(8):833-836, discussion 837 Beaudreuil J, Dieude P, Poiraudeau S, Revel M. Disabling chronic low back pain with Modic type 1 MRI signal: acute reduction in pain with intradiscal corticotherapy. Ann Phys Rehabil Med 2012;55(3):139–147 Freeman BJ, Ludbrook GL, Hall S, et al. Randomized, double-blind, placebo-controlled, trial of transforaminal epidural etanercept for the treatment of symptomatic lumbar disc herniation. Spine 2013;38(23):1986–1994